ÓZBEKSTANDA TOǴAY RESURSLARÍ HÁM OLARDÍ QORǴAW MÁSELELERI - Radjapov, M.Y. (SCIENCE and SOCIETY, 2026)
The article analyzes that forests are the greatest natural resource, and they play an important role in maintaining the ecological balance on our planet by regulating the oxygen levels in the atmosphere.